Author Correction: Glacigenic sedimentation pulses triggered post-glacial gas hydrate dissociation - Jens Karstens (Nature Portfolio, 2018)
The original version of this Article contained an error in the second sentence of the Abstract, which incorrectly read ‘They are stable under high pressure and low, but react sensitively to environmental changes.’ The correct version adds ‘temperature’ after ‘low’. This has been corrected in both the PDF and HTML versions of the Article.